Implementasi Konsep Tropical Paradise pada Interior Fasilitas Rekreasi Keluarga Waterpark - Feilycia Wijaya (Intra, 2016)
Surabaya, capital of East Java, is a place where the legendary battle between a shark (sura) and crocodile (baya) happened. Surabaya has a population of approximately 3 million people with various activities that make Surabaya is a city that never deserted. Various activities were held in Surabaya, which can be visited by the public, especially for families and relatives. One of them is the water games loved by everyone without age limit as an option to spend time with family. The purpose of this design is to provide recreational facilities or water games in Surabaya, surrounded by areas that are fun and offer a tropical feel. This design will give some advantages; such as Surabaya’s people don’t need to travel far away to find family entertainment, and also it will help increase the enthusiasm of people outside to visit Surabaya. The design method used the analytical method, where each thing in the design stage constantly reanalyzed by the study of a particular method. It refers to a design methodology (Jones, 1970) as the formulation of so-called